Archaeoditomotarsus crassitylus, gen. and sp. nov. (Hemiptera: Heteroptera: Acanthosomatidae) from Chile - Faúndez, Eduardo I.; Carvajal, Máriom A.; Rider, David A. (Zootaxa, 2014)
Archaeoditomotarsus crassitylus, gen. and sp. nov. of Acanthosomatidae (Ditomotarsinae: Ditomotarsini), is described and illustrated. The biogeography of the new taxon is discussed and a key to the Chilean genera of Ditomotarsinae is included.